Penerapan Metode AHP untuk Pemilihan Kendaraan Sepeda Motor Matic Studi Kasus Dialer Honda Peranap - Bayu Rianto; Rico Van Halen (RJOCS (Riau Journal of Computer Science), 2016)
In selecting the motorcycle matic, costumers certainly want to get the best and rightchoice. Almost every customer wants an affordable motorcycle matic, fuel efficient, andconvenient to use. Therefore we need a decision support system that can help consumersdetermine the best matic motorcycle in accordance with the wishes of the consumer. Thisdecision support system uses Analytical Hierarchy Process (AHP) as a process in determiningthe best matic motorcycle. Several criteria are used to determine the best matic motorcycle. Inthis study, the test data is obtained from questionnaires and interviews with sources. Theobtained data were tested using expert choice software to determine the best motorcycle matic.This decision support system is expected to help and facilitate the consumers in the selecting thebest matic motorcycle and produce an optimal result which meets the high sense of satisfactionfor the consumer in choosing the best motorcycle matic.